Gender and recovery pathways in the UK. (3rd September 2021) - Andersson, Catrin; Wincup, Emma; Best, David; Irving, Jamie
Abstract: Recovery is now the defining feature of UK drug and alcohol policy. Despite this policy emphasis, little attention has been paid to the lived experience of those in recovery. Instead, research has typically concentrated on treatment populations, which are predominantly male. Consequently, we have little insight into recovery experiences in general, and specifically how they might differ for females and males. This article makes an important contribution through offering a unique insight into the addiction/recovery pathways of 342 female and 410 male participants using data gathered via the UK Life in Recovery survey. Participants were recruited via social media and recovery groups. Bivariate analyses were used to explore gender differences in relation to personal characteristics, addiction and recovery (self-defined), well-being, and family life. These data suggest that a greater proportion of females in recovery report having specific needs in relation to mental health and relationships with children or partners whilst a greater proportion of males disclosed having specific needs in relation to physical health. Whilst the findings reflect the importance of ongoing support for everyone in recovery, they also suggest the need to provide gender-responsive recovery support.